MODULAR TRAINING IN AN ELECTRONIC ENVIRONMENT INFORMATION AND EDUCATIONAL ENVIRONMENT OF EDUCATION (Archive of Conferences, 2020)
The article is devoted to the use of modular training in the electronic information and educational environment of education. Methodological approaches to the use of modular technology and the effectiveness of training with modular technology in education are considered.